Implementation of the Ethical Knowledge in the Higher Economic Education - Daphne Vidanec (Athens Institute for Education and Research, 2014)
As relatively new philosophical discipline, business ethics has sprang out from the business practice in the last quarter of the 20th century. Business ethics is focused on evaluation of business conduction of both individuals and corporations in the business world. Nowadays, in the public and academic milieu of the modern Western societies business ethics is recognized as one of the crucial educational forms, especially in the field of higher economically profiled institutions: faculties of economy, accredited colleges for business and management and the like. Analyzing socio-cultural, political and economic milieu of some European societies that went through certain social, juridical, political and economic metamorphoses since the fall of the Berlin Wall, what we can notice is certain fall of crucial human and social values: social and economic justice, economic equality, social freedom etc. The main task of the business ethics in the field of education is to show how we can build both, individual and social life as rational, socially engaged beings gifted by the capacity of understanding and of reasoning ourselves, our deeds, desires, decisions, choices. In this written elaboration the author tends to investigate and to describe the structure of the ethical education in the contemporary economic higher education through the prism of development and rise of modern economic theory.